Association Between Temporal Muscle Thickness and Survival in Older Patients With Brain Metastases Undergoing Radiation Therapy - Lasse Pikkarainen; Tommi K. Korhonen; Antti Tolonen; Emilia K. Pesonen; Nicole Hernandez; Tanja Skyttä; Otso Arponen (Cancer Reports, 2026)
ABSTRACT Background Finding reliable prognostic markers for patients with brain metastases would be beneficial since they could be used in clinical practice when making treatment decisions. Recent literature has analyzed the role of temporalis muscle thickness (TMT) as a prognostic marker in patients with brain metastases with mixed results. Previous studies have generally focused on patients younger than 65 years. Aims The purpose of this study was to evaluate the effect of TMT measured from head CT scans on the prognosis of patients with brain metastases receiving radiotherapy aged 70 years or older. Methods and Results We identified all patients with brain metastases treated with radiotherapy and measured their TMT from head CT scans at the date of treatment planning CT scans. The patients' demographic data, primary tumor, and treatment allocation were recorded. Sex‐specific cut‐offs for low TMT (males: 4.3 mm, females: 3.975 mm) were determined by maximizing Youden's index for 3‐month survival. We evaluated the association between TMT and 1‐, 3‐, 6‐, and 12‐month overall survival (OS) using Cox proportional hazards modelling. This retrospective study included 249 patients. The mean age of the patients in the cohort was 76.0 ± 4.9 years. Male patients had higher TMT than females (4.7 ± 1.6 vs. 3.7 ± 1.5 mm, p < 0.001). Altogether, 35 (14.1%), 125 (50.2%), 178 (71.5%), and 216 (86.7%) patients had deceased at 1‐month, 3‐month, 6‐month, and 12‐month points, respectively. Although having low TMT was associated with a higher risk of death at 3‐ and 6‐month timepoints (hazard ratio range: 1.41–1.54) in univariate analyses, TMT was not associated with 3‐ or 6‐month survival after adjustment for other clinical factors. Conclusion Low TMT is not an independent marker of lower prognosis in patients aged 70 years or older with brain metastases treated with radiotherapy.